2013
DOI: 10.1007/s11657-013-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis knowledge and attitudes: a cross-sectional study among female nursing school students in Damascus

Abstract: The findings generally reveal poor knowledge about osteoporosis among nursing school female students at Damascus. Integration of osteoporosis in school curricula and public education efforts is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
7
23
0
6
Order By: Relevance
“…Our study findings of osteoporosis knowledge among women of Jazan were also comparable to the findings of other studies. 23 Despite the cultural differences with other studies, women in our study were highly knowledgeable about osteoporosis preventive food items including milk intake, cheese, fish, and eggs. However, women in our study showed less knowledge of exercise as preventive measure of osteoporosis because this specific item in our knowledge measurement might be less relevant to their culture.…”
Section: Discussionmentioning
confidence: 69%
“…Our study findings of osteoporosis knowledge among women of Jazan were also comparable to the findings of other studies. 23 Despite the cultural differences with other studies, women in our study were highly knowledgeable about osteoporosis preventive food items including milk intake, cheese, fish, and eggs. However, women in our study showed less knowledge of exercise as preventive measure of osteoporosis because this specific item in our knowledge measurement might be less relevant to their culture.…”
Section: Discussionmentioning
confidence: 69%
“…The studies were performed in various countries and regions. The majority of the studies are from Saudi Arabia [15,17,18,19], Sri Lanka [20], Canada [21,22,23,24], Thailand [25,26] and South Korea [27,28,29,30], Jordan [31,32], Malaysia [33,34], China [35,36] and the rest are from United States [35], Nigeria [4], Taiwan [37], Syria [38], India [39], Poland [40], Denmark [41], U.K. [42], Iran [43], Pakistan [44], Columbia [45], the Basque region (Spain) [46], Japan [47] and Australia [48]. Most of the studies included in this review used either self-designed or validated questionnaire to assess the knowledge, attitude and practice among subjects regarding bone health/osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies [32,37] involved adolescents in their studies while others included young adult population. Background of the subjects varied among the studies; most of them were students from college [21,37], high school [32,37], polytechnic [4] or university [17,20,31,33,35,38,39,43,44,45]. The fields of study were medical and non-medical.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted among Iranian women showed a direct relationship between calcium intake and perceived susceptibility (r = 0.068, p = 0.003), and a significant inverse relationship with perceived barriers (r = 0.047, p = 0.05) [29]. Sayed-Hassan et al [30] found that calcium intake and perceived barriers were significantly associated, but Edmonds et al [27] found little perceived barriers to calcium intake, low correlation and not significant between calcium intake and perceived barriers to exercise (r = 0.041, p = 0.217). However, cal-cium intake also had a low correlation to perceived benefits of calcium intake that did not reach statistical significance (r = 0.050, p = 0.159).…”
Section: Discussionmentioning
confidence: 99%